Cochlear Implant Practice Patterns: The U.S. Trends with Pediatric Patients. - Hemmingson, Carly; Messersmith, Jessica J. (Journal of the American Academy of Audiology, 2018)
Background: Many factors affect an individual's outcomes with a cochlear implant (CI); however, quality of device programming and consistency of follow-up appointments have been shown to be crucial contributors. As audiologists' CI caseloads increase, time constraints on appointments also increase, thus fueling the need for efficient and effective programming strategies. Currently, there are no standardized guidelines describing what methods should be used during programming, nor are there standardized schedules that delineate what procedures should be performed at specific appointment intervals. Without standardized programming guidelines, clinical practices may be variable and may not align with best practice research; thus, outcomes with a CI, particularly for pediatrics, may not be reflective of the actual potential available. Purpose: The purpose of this study was to identify the clinical practice patterns used by U.S. audiologists when programming and providing follow-up care to children who use CIs. This study aimed to determine the following: common programming approaches, provision intervals for these procedures, common validation assessments, typical follow-up care schedules, and source(s) of CI training. In addition, this study sought to evaluate if training and/or follow-up care differed between small and large CI centers. Research Design: A cross-sectional survey design was used. Study Sample: Target population included practicing audiologists working with pediatric CI users throughout the United States. Participation was voluntary, thus random selection could not be used. A total of 167 participants opened and began the online survey and 113 successfully completed the survey instrument (23.99% return rate). Data Collection and Analysis: Potential participants were identified using the "find a clinic" function on three CI manufacturers' websites. Potential participants were asked to complete an online survey seeking information about practices they employ in their clinical setting. Survey responses were analyzed for trends. Results: Overall, a common follow-up schedule was determined, which included an average of 6.8 appointments within the first year. Minor differences in training and programming practices between small and large CI centers emerged; however, no statistically significant results were noted. Results did reveal trends in the use of certain clinical practices. This was particularly evident in the limited use of objective measures. Conclusions: Overall, the findings support other recent studies that suggest the development of CI guidelines that may standardize programming and follow-up practices of CI audiologists. This could prove valuable for the continual improvement of CI outcomes, particularly in the pediatric population.